(The Effect of Hydrocolloids Addition on The Quality of Low Calorie Pineapple Jam) - Nurlaelyah, Elly; D. Sirait, Shinta; Nuraini, Dhiah (Balai Besar Industri Agro, 2000)
Most pineapple jam found in the market is high calorie food because it ussually contains about 55 percent of sugar. for certain reasons such as obesity prevention and keeping healty, jam can be diversified by reducing is sugar content. this research was aimed at finding out the effects of hydrocoloid addition on the quality of pineapple jam produced. Two kinds of hydrocolloid used i.e. low methoxyl pectin and carboxy methyl cellulose (CMC). as much as 0.9 percent of the pectin or CMC was added into pineapple slurry to produce jam A (CMC) or jam C (low methoxyl pectin). A preference test was carried out to investigate 3 (three) different jams i.e. jam A, pineapple jam purchased from local market (jam B), and jam C. the result showed that jam C had the biggest average score of 3,75 in threms of colour, taste, and flavor, whereas jam B was the least acceptable by 20 panelists with an average score of 3,24. however after 3 months storage the quality of jam A was batter tham jam C physico-chemically and microbiologically. The calorie content of every 100 g of jam A and jam C was 14,80 and 14,90 respectively.